The phylogeny of the genus Indoplanorbis (Gastropoda, Planorbidae) from Africa and the French West Indies. (10th July 2018) - Mouahid, Gabriel; Clerissi, Camille; Allienne, Jean‐François; Chaparro, Cristian; Al Yafae, Salem; Mintsa Nguema, Rodrigue; Ibikounlé, Moudachirou; Moné, Hélène
Abstract: Indoplanorbis exustus is a freshwater snail known as the intermediate host of various trematode parasites, including different species of the genus Schistosoma . Although its genetic diversity is well described in Asia, the phylogenetic diversity of strains from Africa and Guadeloupe (French West Indies) and their relationship to Asian and South‐East Asian strains remain unknown. To tackle this issue, we sampled individuals from Africa and Guadeloupe, and we computed phylogenetic reconstructions using five molecular markers: partial sequences of two mitochondrial genes, cox1 and 16S, and three nuclear markers, ITS1, ITS2 (Internal Transcribed Spacer 1 and 2) and 5.8S. Our results suggest that strains in Africa and Guadeloupe come from Asia and that they all belong to a single clade that is widespread around the globe.